Analysis of Spatial Distribution of Maternal Death Cases in the Special Region of Yogyakarta Province - Yuspita Sari, Rizky; Hernawan, Heri; Sevtiyani, Imaniar; Ariningtyas, Ristiana Eka (Universitas Ibn Khaldun Bogor, 2024)
Maternal mortality is an important indicator of improving health in a country which is included in the target of achieving the Subtainable Development Goals (SDGs). The Maternal Mortality Rate (MMR) in Indonesia in 2018 was still high at around 305/100,000 KH. Maternal mortality in the Yogyakarta Special Region Province experienced a significant increase in 2021. Objective: to analyze the Maternal Mortality Rate (MMR) in the Yogyakarta Special Region Province and determine the relationship between spatial accessibility of Community Health Centers. Method: This is a quantitative descriptive study to see the pattern of distribution of maternal mortality cases using GIS using ArcGis. Results: Maternal deaths in 2020-2022 have a spreading pattern with the highest cases being in Banguntapan sub-district and the distribution of health centers has been evenly distributed in each sub-district. Conclusion: Maternal death cases occur almost in all sub-districts, with a widespread distribution pattern. The highest case in the last three years occurred in 2021 due to exposure to Covid-19. The distribution of health centers is evenly distributed, but hospitals are still concentrated in Sleman district and Yogyakarta city.